Investigation Into The Planar Least Squares Inverse(PLSI) Method Of Stabilizing Two-Dimensional (2-D) Recursive Digital Filters - Gangathran, N. (2007)
The objective of this thesis is to provide a complete solution to the PLSI method of stabilizing recursive digital filters. It is proved in this thesis that if the original unstable 2-D quarter-plane (QP) polynomial and the corresponding PLSI are of the same degree being less than or equal to two, the PLSI polynomial is always stable. Alternatively, if the coefficient matrix [A] of the given unstable polynomial is centrosymmetric, or symmetric and is of order greater than two, then the PLSI polynomial need not be stable.